Analisis Variasi Lanskap Linguistik di Taman Nasional Way Kambas (TNWK) sebagai Daya Tarik Wisata - Doni Alfaruqy; Harits Setyawan (Yayasan Literasi Sains Indonesia, 2026)
The use of appropriate and effective language in public spaces can help provide clear information to tourists. The purpose of this study is to identify the variations of linguistic landscape found in Way Kambas National Park (TNWK) and to determine the language functions reflected in its linguistic landscape. Analysis of the linguistic landscape variations used on signboards, information boards, educational media, and public facilities throughout the tourist area serves as an evaluation of information readability for visiting tourists. This study employs a descriptive qualitative method. The data were collected by photographing public facilities, information boards, signboards, educational media, and warning signs located within the tourist area. Each object was photographed twice, and from the two images obtained, the clearer one was selected. Based on the findings, the most frequently observed linguistic landscape variation in Way Kambas National Park is monolingualism. This indicates that TNWK management needs to anticipate the readability needs both local and international visitors.